An integrated beam-plate structure multi-level optimal design framework based on bi-directional evolutionary structural optimization and surrogate model. (January 2018) - Li, Kai; Yu, Yanyun; He, Jingyi; Lin, Yan
Highlights: An integrated beam-plate structure multi-level optimal design framework is proposed. Dimension optimization, topology optimization and section optimization are covered. Multiple load cases are considered to enhance the practicality. Finite element model is generated automatically to raise the overall efficiency. Small amount of calculation with good convergence property. Abstract: Lots of endeavors have been made to apply optimization techniques to real design problems for various engineering beam-plate structures, however, due to the limitation of traditional topological form and the difficulty of finding the optimal topology in numerous optional design plans, many beam-plate structure designs are not the optimal solution but only a feasible solution. This paper proposes an integrated optimal design framework for beam-plate structure based on combining bi-directional evolutionary structural optimization (BESO) and surrogate model method, which covers three optimization levels, as dimension optimization, topology optimization and section optimization. BESO is used for topology optimization. In order to deal with beam-plate structures, the traditional BESO method is improved by using cubic box as the unit cell instead of solid unit to construct periodic lattice structure. Requirements for the framework are discussed based on the features of beam-plate structure design process first. The proposed framework consists of automated finite element modeling module, structure optimization module and post-processing module. Usefulness of the designed framework is examined through a cantilever beam structure design.